2018
DOI: 10.1021/acscatal.8b00341
|View full text |Cite
|
Sign up to set email alerts
|

An “On-Cycle” Precatalyst Enables Room-Temperature Polyfluoroarylation Using Sensitive Boronic Acids

Abstract: The use of fluorinated arylboronic acid building blocks in cross-coupling has remained challenging, because of their acute base sensitivity. We report a general solution to this problem using a true catalytic intermediate, Pd­(PAd3)­(p-FC6H4)­Br, as a uniquely effective “on-cycle” precatalyst that allows Suzuki–Miyaura coupling to occur much faster than even the most severe protodeboronation side reactions. Control of boron speciation between the active acid and dormant ester forms was also found to play a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 64 publications
1
68
0
Order By: Relevance
“…Carrow applied (Ad 3 P)Pd(4‐C 6 H 4 F)Br ( 26 ) as a highly efficient precatalyst for the SMC of aryl bromides and protolytically sensitive fluorinated arylboron species . Under optimized conditions, the oxidative addition precatalyst 26 was significantly more effective than the catalyst generated in situ (PAd 3 and Pd 2 (dba) 3 ), (PAd 3 )Pd(η 3 ‐cinnamyl)Cl, [(P( t ‐Bu) 3 )PdBr] 2 , G2 SPhos, G3 XPhos, and IPr PEPPSI.…”
Section: Palladium Precatalystsmentioning
confidence: 99%
“…Carrow applied (Ad 3 P)Pd(4‐C 6 H 4 F)Br ( 26 ) as a highly efficient precatalyst for the SMC of aryl bromides and protolytically sensitive fluorinated arylboron species . Under optimized conditions, the oxidative addition precatalyst 26 was significantly more effective than the catalyst generated in situ (PAd 3 and Pd 2 (dba) 3 ), (PAd 3 )Pd(η 3 ‐cinnamyl)Cl, [(P( t ‐Bu) 3 )PdBr] 2 , G2 SPhos, G3 XPhos, and IPr PEPPSI.…”
Section: Palladium Precatalystsmentioning
confidence: 99%
“…In 2018, Carrow et al. treated C 6 F 5 Bpin and C 6 F 5 B(OH) 2 with wet triethylamine (weak base), and found that C 6 F 5 Bpin underwent protodeboronation, but the rate was slower than that for C 6 F 5 B(OH) 2 [8e] . Hence, it can be suggested that the best conditions to synthesize 2,6‐difluorophenyl‐Bpin derivatives are base‐free methods.…”
Section: Resultsmentioning
confidence: 99%
“…Carrow et al . studied the influence of triethylamine and/or water with respect to the stability of C 6 F 5 Bpin and C 6 F 5 B(OH) 2 towards protodeboronation [75] . Notably, triethylamine was used as received and contains trace amounts of water.…”
Section: Protodeboronation Of Fluorinated Aryl Boronatesmentioning
confidence: 99%
“…In 2018, Carrow et al . synthesized a series of unsaturated complexes of the type [Pd(L)(Ar)X], including [Pd(PAd 3 )( p ‐FC 6 H 4 )Br] (Carrow precatalyst; PAd 3 = tri(1‐adamantyl)phosphine), which was found to be an efficient ‘on‐cycle’ precatalyst [75] . This system allowed for the Suzuki‐Miyaura cross‐couplings of highly fluorinated aryl boronic acids with aryl or heteroaryl bromides and proved to be faster than the competing protodeboronation degradation pathway.…”
Section: Applications Of Fluorinated Aryl Boronates In Organic Synthesismentioning
confidence: 99%
See 1 more Smart Citation